2020
DOI: 10.1152/jn.00736.2019
|View full text |Cite
|
Sign up to set email alerts
|

Auditory cortex reflects goal-directed movement but is not necessary for behavioral adaptation in sound-cued reward tracking

Abstract: Recent evidence suggests that sensory cortex represents nonsensory variables such as reward expectation, but the relevance of these representations for behavior are not well understood. We show that rat auditory cortex (AC) is modulated during movement and reward anticipation in a sound-cued reward tracking task, whereas AC inactivation only impaired discrimination without affecting reward tracking, consistent with a predominantly sensory role of AC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 64 publications
2
22
0
Order By: Relevance
“…In humans, choice biases are often smaller than the optimal ( Maddox, 2002 ). This is consistent with the findings in rodents including our study ( Figure 2 ) ( Stoilova et al., 2020 ). In contrast, monkeys had larger choice biases than the optimal ( Feng et al., 2009 ; Teichert and Ferrera, 2010 ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In humans, choice biases are often smaller than the optimal ( Maddox, 2002 ). This is consistent with the findings in rodents including our study ( Figure 2 ) ( Stoilova et al., 2020 ). In contrast, monkeys had larger choice biases than the optimal ( Feng et al., 2009 ; Teichert and Ferrera, 2010 ).…”
Section: Discussionsupporting
confidence: 94%
“…Adding a parameter in the simple psychometric function always increased the log likelihood; the likelihood ratio test investigated whether the additional parameter significantly improved the fitting (Δ log likelihood in Figure 2 D, left) ( Daw, 2011 ; Maddox, 2002 ). We verified that the psychometric function adding the block-dependent decision threshold (block threshold) significantly improved the fitting than the simple psychometric function (likelihood ratio test, p = 1.8 × 10 -10 ) ( Figure 2 D, left), indicating that the asymmetric reward blocks biased the choices as reported in previous studies ( Daw, 2011 ; Lak et al., 2020a ; Nomoto et al., 2010 ; Stoilova et al., 2020 ; Stüttgen et al., 2011 ). We then found that the psychometric function with block-dependent thresholds and duration-dependent sensitivities fit the choices (likelihood ratio test, p = 0.0073), but the parameters for duration-dependent thresholds (p = 0.048), block-dependent sensitivities (p = 0.041), or lapse rate (p = 0.35) did not significantly improve the fitting after Bonferroni correction ( Figure 2 D, right).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations